Desenvolvimento de metodologia para cálculo de perdas elétricas em redes de distribuição de baixa tensão - Strauch, Mariana Torres (2002)
This dissertation presents a probabilistic methodology for the calculation of technical losses in distribution networks. The development was based on typical curves of consumer s load, constructive topology and electrical data from the local Distribution Utility. The proposal methodology uses reduced database, easily obtained from the utility that makes possible the record keeping by regulatory agencies. It takes into consideration the random behaviour of the load, adopting a solution that pays respect, both, to the amount of data needed to represent all electrical characteristics of the system (in terms of time and resources for obtaining and maintaining records) and the accuracy of the results. A software for technical losses calculation was developed, resulting in a flexible tool that allows the user for the calculation of losses either based upon typical parameters or with field measurements data.